Efeito do tratamento com extrato de Ginkgo biloba sobre a sinalização insulinica e inflamatoria em tecido adiposo de ratos com obesidade induzida pela dieta - Hirata, Bruna Kelly Sousa [UNIFESP] (2014)
Obesity is a chronic disease with worldwide incidence, associated with development of metabolic disorder, such as insulin resistance and diabetes Mellitus type 2. It has been suggested that the development of obesity-related insulin resistance is associated to an inflammatory status. In this context, it is highly desirable to discover new therapies to improve insulin sensitivity. The Ginkgo biloba Extract (GbE) is one of the most widely used herbal medicines by the population. Our previous study has demonstrated that GbE was able to improve both insulin sensitivity and signaling pathway. Therefore, the aim of this study was to evaluate the effect of GbE on insulin resistance in adipose tissue of diet-induced obese rats. For this purpose, rats were fed with high fat diet for 2 months and thereafter, they were treated during 14 days with 500mg/kg of GbE. The GbE treatment significantly increased Adipo R1 gene expression and IR, IRS-1 and Akt phosphorylation, while it reduced NF-κB p65 phosphorylation and adipocyte size. The data described above suggest that GbE might have potential as a therapy to prevent or treat obesity-related metabolic complications, especially for obese subjects resistant to adhere to a nutritional education program.